2016
DOI: 10.1016/j.jcot.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hematopoietic progenitor cells in trauma hemorrhagic shock

Abstract: Hemorrhagic shock (HS) is the major cause of death during trauma. Mortality due to HS is about 50%. Dysfunction of hematopoietic progenitor cells (HPCs) has been observed during severe trauma and HS. HS induces the elevation of cytokines, granulocyte-colony stimulating factor (G-CSF), peripheral blood HPCs, and circulating catecholamines, and decreases the expression of erythropoietin receptor connected with suppression of HPCs. Impaired HPCs may lead to persistent anemia and risk of susceptibility to infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Activity of the bone marrow has been shown to be altered by trauma in patients. Severe trauma induces endothelial hyperpermeability, hematopoietic stem and progenitor cell trafficking, anemia, inflammation, compensatory immunosuppression, and bone marrow dysfunction 56,57 . Specifically, Livingston and colleagues have described bone marrow failure, including reduced hematopoietic activity and severe growth defects in bone marrow stromal cells which are a critical component of the hematopoietic niche 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Activity of the bone marrow has been shown to be altered by trauma in patients. Severe trauma induces endothelial hyperpermeability, hematopoietic stem and progenitor cell trafficking, anemia, inflammation, compensatory immunosuppression, and bone marrow dysfunction 56,57 . Specifically, Livingston and colleagues have described bone marrow failure, including reduced hematopoietic activity and severe growth defects in bone marrow stromal cells which are a critical component of the hematopoietic niche 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system, which regulates the body's response to trauma, can directly interact with immune cells through adrenergic receptors . Trauma, HS, and subsequent release of proinflammatory cytokines can result in a sustained increase in circulatory norepinephrine, which can suppress the growth and differentiation of hematopoietic progenitors, particularly erythroid progenitors, and facilitate their mobilization out of the bone marrow . Blocking the adrenergic receptors in Sprague–Dawley rats was shown to restore progenitor function .…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 Recent studies shown mobilization of HPCs from BM in peripheral blood cells associated with the poor outcome in patients with T/HS. 1 Multiple factors are involved in the HF and not just the mobilization of HPCs from bone marrow in to peripheral blood. Elevated cytokines, Granulocyte colony stimulating factor (G-CSF), norepinephrine levels and decreased the expression of erythropoietin receptor (EpoR) also contributed the hematopoietic failure in T/HS Patients (Fig.…”
Section: Hematopoietic Failure and T/hsmentioning
confidence: 99%
“…Elevated serum cytokines (TNF-a, IL-6) levels, granulocyte colony stimulating factor (G-CSF), catecholamine, mobilization of hematopoietic progenitor cells (HPCs) from bone marrow in to peripheral blood cells and decreased expression of erythropoietin (EPO-R) receptor are also associated with HF among T/HS. 1 , 2 Advanced care and treatment of the traumatic injured and haemorrhage patients has undergone much progress in the last decades. Resuscitation fluid, blood and its components are used for the control of haemorrhage.…”
Section: Introductionmentioning
confidence: 99%